PF-6 Risk Factors Investigation of Classical Swine Fever (CSF) in the District of Sikka, Flores Island Indonesia - Petrus Malo Bulu; Ewaldus Wera; Margaretha Siko (Hemera Zoa, 2018)
The existence of CSF in an area and the potential for introducing the disease into a new area can be associated with the presence of certain risk factors. Identification of these risk factors is important in understanding the transmission of disease and for the development of effective prevention, control and eradication programs. An epidemiological investigation will be carried out on small-holder farmers in the District of Sikka Flores Island, Indonesia. The study is designed to identify factors associated with seropositivity to Classical swine fever (CSF). Classical Swine Fever is a serious and highly infectious viral disease of domestic pigs and wild boar (1). It remains one of the most important transboundary viral diseases of swine worldwide (2).